Verse Rhetoric in the Name of Allah in the Qur'an: An Example of the Perpetrator - Öğretim Üyesi Eid Abdulaziz (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2023)
Purpose: This paper aims to examine the word of Allah or Lafz Jalalah as the perpetrator in the Qur’an. On the other hand, this research also deals with Lafzatullah, who is used as the perpetrator, in the context of grammar and language philosophy. Design/ methods/approach: The research uses qualitative methods with the word of Allah or Lafz Jalalah in the Qur’an as the primary focus. The data source used in the study originated from the Qur’an in term of Allah or Lafz. To analyze the word of Allah or Lafz Jalalah in the Qur’an, the author uses a semantic word of Allah, used at two levels as a clear noun and a pronoun. Findings: The semantic approach in this research study confronted with countless facets of eloquence and rhetoric in the name